2018
DOI: 10.1177/1081286518758356
|View full text |Cite
|
Sign up to set email alerts
|

On high-order approximations for describing the lagging behavior of heat conduction

Abstract: This paper is dedicated to high-order effects of thermal lagging in correlation with heat transfer models in micro- or nanoscale, relating the number of energy carriers and the associated resonance phenomenon under high-frequency excitations. Thus, a class of constitutive equations is considered for the heat flux describing high-order effects in the lagging behavior of heat transport. Tzou’s model, which is based on time-differential dual-phase-lag approximations of heat conduction, is generalized, incorporati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…Quintanilla and Racke 44 observed that there an area of influence result when , however when they have founded some spatial approximations explaining the Phragmén–Lindelöf alternative. It is worth noting that our choices of the HOTD parameters are capable to involve several models of heat conduction: when we take , we have a diffusive behavior; but by taking , we get a wavelike behavior 6 , 30 .…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quintanilla and Racke 44 observed that there an area of influence result when , however when they have founded some spatial approximations explaining the Phragmén–Lindelöf alternative. It is worth noting that our choices of the HOTD parameters are capable to involve several models of heat conduction: when we take , we have a diffusive behavior; but by taking , we get a wavelike behavior 6 , 30 .…”
Section: Numerical Resultsmentioning
confidence: 99%
“…In one of these efforts, Abouelregal 27 29 introduced some generalized models of heat conduction including higher-order time-derivative. Earlier, Chiriţă 30 investigated the high-order Fourier law to illustrate the lagging performance of heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…On the other side the spatial behavior of the transient solutions, for the model in concern, was established by Chiriţă [5]. It was shown there that (a) for n = m + 1 there was established an influence domain result (the corresponding constitutive equation describes the wave behavior), while (b) for n = m there was established some exponential decay estimates of the Saint-Venant type (the corresponding constitutive equation describes the diffusive behavior), without any restriction on the coefficients of the constitutive equation (2) other than a n b m > 0 .…”
Section: Concluding Discussionmentioning
confidence: 99%
“…The way in which the heat-affected zone enlarges in the time-history, however, is an unknown to be determined. A study on this question can be found in the paper by Chiriţă [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation